Rhamnan sulfate reduces atherosclerotic plaque formation and vascular inflammation. (December 2022) - Patil, Nikita P.; Gómez-Hernández, Almudena; Zhang, Fuming; Cancel, Limary; Feng, Xu; Yan, Lufeng; Xia, Ke; Takematsu, Eri; Yang, Emily Y.; Le, Victoria; Fisher, Megan E.; Gonzalez-Rodriguez, Agueda; et al.
Abstract: Objective: While lipid-lowering drugs have become a mainstay of clinical therapy these treatments only slow the progression of the disease and can have side effects. Thus, new treatment options are needed to supplement the effects of lipid lowering therapy for treating atherosclerosis. We examined the use of an inexpensive and widely available marine polysaccharide rhamnan sulfate as an oral therapeutic for limiting vascular inflammation and atherosclerosis. Methods and results: We found rhamnan sulfate enhanced the barrier function of endothelial cells, preventing the deposition of LDL and maintaining barrier function even in the presence of glycocalyx-degrading enzymes. Rhamnan sulfate was also found to bind directly to FGF-2, PDGF-BB and NF-κB subunits with high affinity. In addition, rhamnan sulfate was a potent inhibitor of NF-κB pathway activation in endothelial cells by TNF-α. We treated ApoE −/− mice with a high fat diet for 4 weeks and then an addition 9 weeks of high fat diet with or without rhamnan sulfate. Rhamnan sulfate reduced vascular inflammation and atherosclerosis in both sexes of ApoE −/− mice but had a stronger therapeutic effect in female mice. Oral consumption of rhamnan sulfate induced a significant decrease in cholesterol plasma levels in female mice but not in male mice. In addition, there was a marked reduction in inflammation for female mice in the liver and aortic root in comparison to male mice. Conclusions: Rhamnan sulfate has beneficial effects in reducing inflammation, binding growth factors and NF-κB, enhancing endothelial barrier function and reducing atherosclerotic plaque formation in ApoE −/− mice.